2014
DOI: 10.1080/07370024.2014.924412
|View full text |Cite
|
Sign up to set email alerts
|

Interactivity Improves Usability of Geographic Maps for Visually Impaired People

Abstract: International audienceTactile relief maps are used by visually impaired people to acquire mental representation of space, but they retain important limitations (limited amount of information, braille text, etc.). Interactive maps may overcome these limitations. However, usability of these two types of maps had never been compared. It is then unknown whether interactive maps are equivalent or even better solutions than traditional raised-line maps. This study presents a comparison of usability of a classical ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 48 publications
3
97
1
5
Order By: Relevance
“…A previous project on a similar topic had involved specialized teachers and visually impaired people in the design process, but not children (Brock et al 2015). The results show that the device improved usability and satisfaction.…”
Section: Motivation and Objectivessupporting
confidence: 49%
“…A previous project on a similar topic had involved specialized teachers and visually impaired people in the design process, but not children (Brock et al 2015). The results show that the device improved usability and satisfaction.…”
Section: Motivation and Objectivessupporting
confidence: 49%
“…In another study, Brock et al (2014) designed gestural interaction techniques that enable a blind user to choose between different types of information, retrieving the names or detailed information about points of interest, or measuring the distance between them. In a follow-up study, Brock et al (2015) demonstrated that, compared to classical raised-line maps, interactive tactile maps improve efficiency and user satisfaction in a map exploration task. One of the main limitations of interactive tactile maps is that they require the manual production of raised-line overlays, which is a timeconsuming process.…”
Section: Better Accessibility With Interactive Audio-tactile Mapsmentioning
confidence: 99%
“…Legends were structured around the different types of geographical information. In general, when discovering a new tactile map, visually impaired people first read the legends [27]. Similarly, in the prototype, students can go through the first menu, and then read the content within each category (second menu).…”
Section: Interaction Principlesmentioning
confidence: 99%
“…MapSense was based on an interactive audio-tactile map illustrated in Figure 1, and initially designed by [27]. Its main components are a raised-line map overlay placed over a 27-inch touch screen using capacitive projected technology, connected to a computer and speakers.…”
Section: General Setupmentioning
confidence: 99%
See 1 more Smart Citation